Can-can - Lang, Walter (20th Century Fox Home Entertainment, 1960)
Based on the hit Broadwat show, this rollicking romantic musical with its spirited dance numbers, lavish costumes and memorable Cole Porter songs is truly high-kicking entertainment. The naughty can-can is against the law in late 19th century Paris, but a vivacious cafe owner (Shirley MacLaine) lets her girls perform it anyway. With the help of her clever boyfriend/lawyer (Frank Sinatra), she manages to keep a corrupt judge (Maurice Chevalier) looking the other way - until a new judge (Louis Jourdan) vows to end the shocking behaviour.